The GT1-TPS Structural Domain Protein From Haemonchus contortus Could Be Suppressive Antigen of Goat PBMCs - Wen, Zhaohai; Aleem, Muhammad Tahir; Aimulajiang, Kalibixiati; Chen, Cheng; Liang, Meng; Song, Xiaokai; Xu, Lixin; Li, Xiangrui; Yan, Ruofeng (Frontiers in Immunology, 2022)
Trehalose phosphate synthase (TPS), a key enzyme in trehalose synthesis, is not present in mammals but critical to the viability of a wide range of lower organisms. However, almost nothing is known about the function of Hc-TPS (GT1-TPS structural domain protein from Haemonchus contortus). In this study, Hc-TPS gene was cloned and the recombinant protein (rHc-TPS) was expressed and purified. The quantitative real-time PCR (qPCR) results showed that Hc-TPS was transcribed at different stages of H. contortus, with higher levels of transcription at the molting and embryo stages. Immunofluorescence analysis showed that Hc-TPS was widely distributed in adults, but the expression was mainly localized on the mucosal surface of the intestine as well as in the embryos of female worms. The impacts of rHc-TPS on peripheral blood mononuclear cell (PBMC) proliferation, nitric oxide (NO) generation, transcriptional expression of cytokines, and related pathways were examined by co-incubating rHc-TPS with goat PBMCs. The results showed that rHc-TPS significantly inhibited PBMC proliferation and NO secretion in a dose-dependent manner. We also found that rHc-TPS activated the interleukin (IL)-10/signal transducer and activator of transcription 3/suppressor of cytokine signaling 3 (IL-10/STAT3/SOCS3) axis and significantly promoted SOCS3 expression, while inhibiting interferon-gamma (INF-γ), IL-4, IL-9, and IL-2 pathways. Our findings may contribute to understanding the immune evasion mechanism for the parasite during host–parasite interactions and also help to provide ideas for discovering new drug targets.